The Different Faces of Angioedema: Classification, Diagnosis and Management - Mariana Batista; F. Alves; Margarida Gonçalo (Sociedade Portuguesa de Dermatologia e Venereologia, 2019)
Angioedema is a transient localized and self-limiting edema of the subcutaneous and submucosal tissue, due to the release of vasoactive mediators. However, different mechanisms are at the origin of the different types of angioedema (acute or chronic, related or not with mast cell mediators and genetic and familial or acquired). Dermatologists should be able to recognize the different forms of angioedema as associated symptoms, treatment and prognostic factors are completely different. This paper reviews the classification of angioedema, diagnostic tests and management.